The Mountain and the Book. Three Written Libraries in Meran - Perottoni, Davide (Writingplace, 2018)
Literature has the ability to grasp atmospheres, to look at things from many points of view, to deal with the pragmatic as well as the poetic, with creativity and subjectivity; these and other qualities offer a wealth of possibilities to design. This graduation project tried to define both the possibilities offered and the ways in which to employ them in the traditional design process. In doing so, literature was both a tool to understand and to create, a method to engage the mind and fuel creativity. Throughout the different phases, it is a tool to read, to write and to continuously challenge all the elements of a design, from analysis to scenario, from site to detail. In this way, the two key elements of the project, the mountain and the book, were defined and declined in the design of three libraries in the area of Meran in the Italian Alps. The literary tool, in all its declinations, is also employed as a different way to engage one’s own creativity; it provides both a rational way to explore and deal with space and a poetic view that ‘illuminates’ the design task and allows to deal with inspiration and concepts in a varied and versatile way. Literature being an added tool to the design process, the literary material is constantly confronted with design through graphical means in a loop process. In this approach, the designer acts as an authoring medium between the site and the design that has to take place in it.